Pengaruh Pertumbuhan Penjualan, Financial Distress dan Ukuran Perusahaan Terhadap Penghindaran Pajak - Damayanti, Damayanti; Hari Stiawan (AKUA: Jurnal Akuntansi dan Keuangan, 2023)
This study aims to determine the effect of Sales Growth, Financial Distress, and Company Size on Tax Avoidance. The type of research used in this study is a type of associative quantitative research. Data collection techniques use secondary data in the form of financial reports that have been published through the Indonesia Stock Exchange (IDX). The collected data was processed using the Eviews program version 9. The population used in this study were LQ-45 companies listed on the Indonesia Stock Exchange (IDX) during the 2017-2021 period. The sample selection technique used a purposive sampling technique and obtained as many as 18 companies for 5 years with a total sample data obtained of 90 sample data. The data analysis method used in this research is descriptive analysis and multiple linear regression. The results showed that partially the variable sales growth, financial distress and company size had an effect on Tax Avoidance. While simultaneously the variable sales growth, financial distress and firm size together influence the expected Tax Avoidance.